Sprint Specificity of Isolated Hamstring-Strengthening Exercises in Terms of Muscle Activity and Force Production - Prince, Caroline; Morin, Jean-Benoît; Mendiguchia, Jurdan; Lahti, Johan; Guex, Kenny; Edouard, Pascal; Samozino, Pierre (Frontiers in Sports and Active Living, 2021)
To train hamstring muscle specifically to sprint, strengthening programs should target exercises associated to sprinting horizontal force production and high levels of hamstring activity. Therefore the objectives of this study were to analyse the correlation between force production capacities during sprinting and hamstring strengthening exercises, and to compare hamstring muscle activity during sprinting and these exercises. Fourteen track and field athletes performed two maximal 50-m sprints and six strengthening exercises: Nordic hamstring exercises without and with hip flexion, Upright-hip-extension in isometric and concentric modalities, Standing kick, and Slide-leg-bridge. The horizontal force production capacity at low (F0) and high (V0) speeds was computed from running velocity data. Force production performances were recorded directly or indirectly during isolated exercises. Hamstring muscular activity (via electromyography) was recorded during all tasks. Our results demonstrate substantially large to very large correlations between V0 and performances in the Upright-hip-extension in isometric (rho=0.56; p=0.040), Nordic hamstring exercise without hip flexion (rho=0.66; p=0.012) and with 90° hip flexion (rho=0.73; p=0.003) and between F0 and Upright-hip-extension in isometric (rho=0.60; p=0.028) and the Nordic hamstring exercise without hip flexion (rho=0.59; p=0.030). However, none of the test exercises activated hamstring muscles more than an average of 60% of the maximal activation during top-speed sprinting. Finally, hamstring muscle-exercises programs aiming to be sprint-specific in terms of horizontal force production could include exercises such as the Upright-hip-extension and the Nordic hamstring exercise, in addition to maximal sprinting activity, which is the only exercise leading to high levels of hamstring muscle activity.